Damping Effects on the Transverse Motions of Axially-loaded Beams Carrying Uniform Distributed Load - Ogunbamike, Oluwatoyin Kehinde (Applications of Modelling and Simulation, 2021)
In this study, the dynamic analysis of a clamped-clamped Rayleigh beam under moving distributed loads is investigated. The solution technique is based on the generalized finite integral transform and a modification of the Struble’s asymptotic technique. Analytical solutions and numerical analysis showed that higher values of axial force, damping due to strain resistance and rotatory inertia reduce the response amplitudes of the beam. It is observed that the influence of structural parameters such as axial force, mass ratio and viscous damping have significant effects on the transverse motion and the critical velocity of the elastic structure carrying moving distributed load. Furthermore, it is also found that for the same natural frequency, the critical velocity for the moving distributed mass problem is smaller than that of moving distributed force problem. Hence resonance conditions for the moving distributed mass problem are reached prior to those of moving distributed force problem. Finally, the accuracy of the solutions obtained is numerically validated by comparison studies with other available cases in literature.